2017
DOI: 10.1080/10641963.2016.1226895
|View full text |Cite
|
Sign up to set email alerts
|

Effects of indomethacin on prostanoid synthesis and vasomotor responsiveness in endothelium-denuded abdominal and thoracic aortas of Wistar rats

Abstract: In endothelium-denuded abdominal (but not thoracic) aortas of rats, the nonselective cyclooxygenase (COX) inhibitor, indomethacin, suppressed contractions evoked by α-adrenergic agonists hypothetically mediated by prostanoids. We aimed to identify these non-endothelial-derived contractile prostanoids released by α-adrenergic receptors activation. Endothelium-denuded abdominal and thoracic aortas of Wistar rats were used for biochemical and functional analyses. Western blot analysis showed that COX-1 and COX-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
2
0
1
Order By: Relevance
“…It is true that the difference in response between control and AIA animals was smaller in the presence of indomethacin. However, this was due to an expected COX-independent reduction in contractile responses to phenylephrine in the aortas obtained of control animals (27), but without a noticeable change in the pattern of these responses in the AIA animals. 1).…”
Section: Discussionmentioning
confidence: 80%
“…It is true that the difference in response between control and AIA animals was smaller in the presence of indomethacin. However, this was due to an expected COX-independent reduction in contractile responses to phenylephrine in the aortas obtained of control animals (27), but without a noticeable change in the pattern of these responses in the AIA animals. 1).…”
Section: Discussionmentioning
confidence: 80%
“…It has been shown that indomethacin reduced the vascular response to αadrenoceptor agonists in the endothelium-denuded aorta of rat, which could be due to the prevention of vasoconstrictor PGs formation in smooth muscles of aorta by COX-2. (Lopez et al, 2017). Since indomethacin inhibits the release of PGs, it is possible to speculate that the availability of PGs may influence the contractile responses (Jaimes et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Os prostanóides também estão intimamente relacionados com a hiporresponsividade vascular provocada pela sepse, uma vez que são importantes moduladores do tônus vascular tanto em condições fisiológicas, como fisiopatológicas (Lopez et al, 2017). No presente estudo, observamos que ao utilizar indometacina e RO1138452, ocorreu a reversão do aumento da ação anti-contrátil do PVAT observado durante a sepse.…”
Section: Discussão 6 Discussãounclassified